2021
DOI: 10.1016/j.jamda.2021.08.032
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 B 1.1.7 Variant Outbreak in a Fully Vaccinated Nursing Home—Madrid, June 2021

Abstract: A SARS-CoV-2 B.1.1.7 variant outbreak has occurred in a fully vaccinated NH and managed by different stakeholders. Among 47 assisted residents, 93.5% presented reactive IgG against Spike protein and 46.8% had COVID-19 infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 6 publications
3
8
0
Order By: Relevance
“…Older adults living in nursing homes, even though vaccinated, may still be at high risk for a complicated bout of COVID-19, given their age, frailty, and need for care. These breakthrough infections of older adults, but not members of the staff, have been previously reported [22]. Greater age is related to lower response to SARS-CoV-2 vaccination Linear regression analysis including age, sex, personal status (resident or staff), and serological evidence of COVID-19 (positive IgG-N) showed that IgG-S concentration after vaccination was associated with age (OR: −0.03 per 10 years-old (95% CI, −0.04 to −0.02 [p < 0.001]) and evidence of past COVID-19 (OR: 1.14 (95% CI, 1.08 to 1.20 [p < 0.001]) (Table 2).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Older adults living in nursing homes, even though vaccinated, may still be at high risk for a complicated bout of COVID-19, given their age, frailty, and need for care. These breakthrough infections of older adults, but not members of the staff, have been previously reported [22]. Greater age is related to lower response to SARS-CoV-2 vaccination Linear regression analysis including age, sex, personal status (resident or staff), and serological evidence of COVID-19 (positive IgG-N) showed that IgG-S concentration after vaccination was associated with age (OR: −0.03 per 10 years-old (95% CI, −0.04 to −0.02 [p < 0.001]) and evidence of past COVID-19 (OR: 1.14 (95% CI, 1.08 to 1.20 [p < 0.001]) (Table 2).…”
Section: Discussionsupporting
confidence: 59%
“…Older adults living in nursing homes, even though vaccinated, may still be at high risk for a complicated bout of COVID-19, given their age, frailty, and need for care. These breakthrough infections of older adults, but not members of the staff, have been previously reported [22]. Greater age is related to lower response to SARS-CoV-2 vaccination [9].…”
Section: Discussionsupporting
confidence: 55%
“…27,38e40 Increasingly, SARS-CoV-2 outbreaks in nursing home populations reflect circulating variants of concern, tied closely to strains circulating in the wider community. This includes documented outbreaks in nursing homes of the delta, 41,42 gamma, 43,44 alpha, 45,46 and beta 47,48 strains. Although early epidemiologic data for the Omicron variant suggest increased risk of infection and milder disease course compared to other variants of concern in vaccinated or previously infected individuals, the full impact of the Omicron variant on nursing homes is not currently clear.…”
Section: Breakthrough Infections Postvaccination and Emergence Of Var...mentioning
confidence: 99%
“…In many countries, morbidity and mortality due to the SARS‐CoV‐2 viral illness have been high among older adults residing in communal living environments, such as Nursing Homes (NHs). 1 , 2 , 3 , 4 , 5 Accordingly, once COVID‐19 vaccines became available in Canada, they were strategically prioritized for NH residents and healthcare providers. 6 In Canada, NHs are regulated residential facilities providing 24‐h nursing care and health services to residents by healthcare personnel.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 To date, most studies on vaccine efficacy in NHs were performed prior to the emergence of the BA.2 variant of SARS-CoV-2 (Omicron) as the dominant strain, and before a third vaccine dose was recommended. [2][3][4][5]9 Moreover, many of these nursing home studies looked at primarily urban as opposed to rural NH populations. 10,11 This report analyzes the effect of prior vaccination of NH residents during recent outbreaks of SARS-CoV-2 in NHs in rural Manitoba, Canada.…”
Section: Introductionmentioning
confidence: 99%